Dnevnik kot literarnozgodovinski vir - Perenič, Urška (Slavistična revija, 2019)
In this article, I am interested in the diary as a type of documentary material and the function of this material for the purpose of literary research. First, I introduce the diary as part of a group of similar sources, among which are letters, memoirs, polemical writings, essays, notes, evaluations, notebooks, authors' documentary material, etc. Then I consider the use of archival material in (Slovenian) literary historiography from the standpoint of different methods. I look at the diary through Winfried Schulze's conception of ego documents, primarily formulated under the influence of the cultural turn and encouraging the inclusion of literary science in the area of cultural studies. Using the example of an intimate diary, I offer a draft of a typology of functions for employing diaries in research. In addition, I present fresh transcripts and previously unpublished Slovenian translations of fragments from the author's German diary.
Keywords: archival material; arhivsko gradivo; biografika; biographies; ego documents; ego dokumenti; German literature in Slovenia; intimate diary; intimni dnevnik; nemška književnost na Slovenskem; Pesjak, Luiza; Stanovsko gledališče v Ljubljani